Tinjauan Yuridis Terhadap Wacana Pembentukan Kabupaten Gunung Sahilan Darussalam Berdasarkan Undang-Undang Nomor 23 Tahun 2014 Tentang Pemerintahan Daerah - Randa Trianto; Mexsasai Indra; Dessy Artina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
The regional growth is a process of solving the region, from a region of the province, district or city to more than one region, then in Act No. 23 of 2014 made clear that the regional growth not only be interpreted as the formation of new regions but may include merging some districts / cities different. Expansion of the territory which was then referred to as the formation of new regions is the division of administrative authority that is accompanied by a delegation of the financing, the division of an area along the natural resources contained therein and the number of residents, Post-New Order shows that decentralization should be a means to maintain the Unitary Republic of Indonesia ( NKRI). This is the reason Rantau Kampar Kiri to bloom from its parent region KamparIn this study, the research is juridical empirical sociological or legal research, legal research or empirical juridical or sociological research, primary data collection in the field to examine how the readiness of the Overseas Kampar Kiri Siak Hulu into autonomous regions.Based on the exposure of research results that refer to Law Number 23 Year 2014 About Local Government and operational guidelines in Government Regulation No. 78 of 2007, there are two main issues, first: the desire of regional expansion Rantau Kampar Kiri Siak Hulu to become an autonomous region has been sixteen years walk but until now there has been too divided, the second: from the physical requirements and administrative conditions contained in Law No. 23 of 2004, has been fulfilled but the New Autonomous Region (DOB) has not been realized.Suggestions from the author: the first President immediately issued a government regulation on the establishment of new autonomous regions, which refers to Law No. 23 of 2014, the central government and regional governments are expected to launch this regional expansion. Both Need for Government Overseas Kampar Kiri Siak Hulu carry out dissemination to the public in connection with the achievement of the development process of the formation of the district of Mount Sahilan Darussalam so that the public is not yet clear ingested issues related to the expansion truth Rantau Kampar Kiri Siak Hulu